Health Education in Narcotics, Psychotropics and Addictive in Mts Miftahul Ulum Bandar Lampung - Dian Utama Pratiwi Putri; Tubagus Erwin Nurdiansyah; Febria Listina (Jurnal Peduli Masyarakat, 2020)
The problem of abuse of Narcotics, Psychotropic and Other Addictive Substances (NAPZA) or popular terms known to the public as Narcotics (Narcotics and Substance / Drug) is a very complex problem, which requires a comprehensive countermeasure effort involving multidisciplinary cooperation, multisector, and its role and the community is actively carried out continuously, consistently and consistently. Although in Medicine, most Narcotics, Psychotropic and other addictive substances (NAPZA) are still beneficial for treatment, but if abused or used not according to medical indications or treatment standards even more so if accompanied by illegal circulation, it will have a very detrimental effect on individuals and society especially young generation. Community service aims to increase the knowledge of teenagers, especially boys, about the dangers of narcotics, psychotropic substances and addictive substances. The method used is health education using written and pictorial material. And the question and answer session as a feed back of health education. The results obtained are children in MTs Miftahul Ulum Bandar Lampung better understand the dangers of narcotics, psychotropic substances and addictive substances